Consumer Search and Market Equilibria: A Note - Braverman, Avishay; Dixit, Avinash (Review of Economic Studies, 1981)
Journal Article Consumer Search and Market Equilibria: A Note Get access Avishay Braverman, Avishay Braverman The World Bank Search for other works by this author on: Oxford Academic Google Scholar Avinash Dixit Avinash Dixit Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 657–658, https://doi.org/10.2307/2297205 Published: 01 October 1981 Article history Received: 01 June 1981 Accepted: 01 July 1981 Published: 01 October 1981